A double dilemma: treatment of stage IV fetal twin-twin transfusion syndrome in the setting of maternal recurrent venous thromoembolism: a case report - Claire M. McCarthy; Alya al-Madhani; Suzanne Smyth; Nóirín E. Russell; Ruwan Wimalasundera; Keelin O'Donoghue (BMC, 2019)
Abstract Background Fetal conditions can pose significant challenges in the management of pregnancies complicated by pre-existing maternal medical conditions. Case presentation We report a case of a 34-year-old woman with Stage IV Twin Twin Transfusion syndrome in the presence of maternal recurrent complex venous thromboembolic disease. Following a previous pregnancy loss, complicated by a third episode of thromboembolic disease, an inferior vena cava filter was placed. One month later, a pregnancy was confirmed and subsequently identified as a monochorionic twin pregnancy. Twin-Twin Transfusion syndrome was identified at 18 weeks' gestation and progressed rapidly to Quintero Stage IV. In consultation with a multi-disciplinary international team, fetoscopic laser photocoagulation was performed. The pregnancy progressed to delivery of female infants at 33 weeks gestation, who have achieved all developmental milestones at 2 years of age. Conclusions We describe the multi-disciplinary effort to optimise the maternal condition to allow fetoscopic laser photocoagulation and continued management of the maternal and fetal conditions to a successful pregnancy outcome.